Material Characterization and Technological Properties of Biocompatible Ti-12Al-42Nb Spherical Powder Alloy for Additive Manufacturing of Personal Medical Implants - Alexander Anokhin; Andrey Kirsankin; Elena Kukueva; Alexander Luk’yanov; Maria Chuvikina; Elena Ermakova; Svetlana Strelnikova; Stepan Kupreenko (Metals)
The paper focuses on material characterization and technology properties of a new Ti-12Al-42Nb spherical powder alloy for additive manufacturing of personal medical implants. The electrode induction melting inert gas atomization (EIGA) method was used to produce the powder alloy. The powder sphericity coefficient (PSC) was 1.02. Image J software was used to calculate the spherical degree by processing images sets from scanning electron microscopy (SEM) and optical microscopy (OM). SEM of particles cross-sections indicated internal thermal-induced porosity (TIP) with a 2.3 μm pore diameter. Particle size distribution was in the range from 15.72 μm (d10) to 64.48 μm (d100) as measured by laser particle analyzer. It was indicated that flowability and powder bulk density were 196 sec and 2.79 g/cm3, respectively. XRD analysis confirmed the beta phase of the powder alloy with no additional phases. X-ray fluorescence spectrometry confirmed the alloyed composition. Reducing and oxidative melting methods of analysis showed a slight amount of impurities: oxygen (0.0087 wt.%), nitrogen (0.03 wt.%), hydrogen (0.0012 wt.%), sulfur (0.0016 wt.%), and carbon (0.022 wt.%). Simultaneous thermal analysis (STA) was performed to indicate weight growth and losses and thermal effects in argon, nitrogen, and air as well as the oxidation of Al2O3, TiO2, and Nb2O5 on the surface layer of Ti-12Al-42Nb powder alloy particles. Different phase transformations of γAl2O3 <semantics>→</semantics> θAl2O3 <semantics>→</semantics> αAl2O3 and TiO2 rutile <semantics>→</semantics> TiO2 anatase phase transformation were detected by STA in the oxidative layer.